2014
DOI: 10.1016/j.clnu.2013.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional status predicts preterm death in older people: A prospective cohort study

Abstract: Nutritional status predicts preterm death in older people: a prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 20 publications
2
52
0
2
Order By: Relevance
“…Indeed, the association between malnutrition and mortality has been recently confirmed by the application of MNA to a cohort of aged people admitted to hospital and followed for 50 months [25]. In that study, the survival rate was significantly lower for malnourished individuals who showed more than doubled difference in the hazard ratio for all causes of death compared to at risk subjects.…”
Section: Age (Years)mentioning
confidence: 88%
“…Indeed, the association between malnutrition and mortality has been recently confirmed by the application of MNA to a cohort of aged people admitted to hospital and followed for 50 months [25]. In that study, the survival rate was significantly lower for malnourished individuals who showed more than doubled difference in the hazard ratio for all causes of death compared to at risk subjects.…”
Section: Age (Years)mentioning
confidence: 88%
“…Sarcopenia and undernutrition are both associated with higher care costs and several adverse health outcomes, namely poor quality of life, prolonged length of stay in hospital and mortality . Routine undernutrition identification is increasing in the clinical practice, but sarcopenia remains poorly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is common among older persons, especially those who are living in nursing homes (malnourished: 8.7%; at risk: 47.5%) and in hospitals (malnourished: 22.0%; at risk: 45.6%) (Cereda et al, 2016). Preventing malnutrition is important, as it is associated with severe consequences in older age, such as poor subjective health (Olin, Koochek, Ljungqvist, & Cederholm, 2005;Rasheed & Woods, 2014), decreased functional ability (Dent, Visvanathan, Piantadosi, & Chapman, 2012;Olin et al, 2005), morbidity (Green & Watson, 2006) and increased risk of earlier death (Dent et al, 2012;S€ oderstr€ om, Rosenblad, Adolfsson, Saletti, & Bergkvist, 2014). The association between oral health and nutrition has previously been described, such as the important prerequisite of the ability to chew and swallow for a healthy nutritional status in older persons (Andersson, Westergren, Karlsson, Rahm Hallberg, & Renvert, 2002;Batchelor, 2015;Cowan, Roberts, Fitzpatrick, While, & Baldwind, 2004;Nieuwenhuizen, Weenen, Rigby, & Hetherington, 2010;Pezzana et al, 2015;Pirlich & Lochs, 2001;Sheiham et al, 2001;Westergren et al, 2002).…”
Section: Introductionmentioning
confidence: 99%